Management of a Traumatic Flap Dislocation Seven Years after LASIK - Majid Moshirfar; Erik Anderson; Nathan Taylor; Maylon Hsu (Case Reports in Ophthalmological Medicine)
Seven years after uneventful laser in situ keratomileusis (LASIK), a 48-year-old woman presented one week after being hit with an iron cord with blurry vision, pain, and irritation. The injury resulted in traumatic flap dislocation, epithelial ingrowth, and macrostriae. Following epithelial removal, the flap was refloated and repositioned. Nine interrupted sutures were used to secure the flap. Three-weeks after surgery with no sutures remaining, the epithelial ingrowth and macrostriae had resolved with a visual acuity of 20/20.